2003
DOI: 10.1073/pnas.1935988100
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide bond formation involves a quinhydrone-type charge–transfer complex

Abstract: The chemistry of disulfide exchange in biological systems is well studied. However, the detailed mechanism of how oxidizing equivalents are derived to form disulfide bonds in proteins is not clear. In prokaryotic organisms, it is known that DsbB delivers oxidizing equivalents through DsbA to secreted proteins. DsbB becomes reoxidized by reducing quinones that are part of the membranebound electron-transfer chains. It is this quinone reductase activity that links disulfide bond formation to the electron transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 30 publications
3
54
0
1
Order By: Relevance
“…An outstanding concern that should be addressed to solve these problems will be the role played by quinone molecules. Our recent findings (11) and those of Regeimbal et al (18) that DsbB-bound UQ assumes an anomalous state with a strong absorption peak at ϳ500 nm seem to provide important clues to the last question. Whereas Regeimbal et al showed that UQ in purified DsbB preparations exhibits a quinhydrone-like color, we provided compelling evidence that only special states of DsbB are able to elicit a UQ spectroscopic transition.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…An outstanding concern that should be addressed to solve these problems will be the role played by quinone molecules. Our recent findings (11) and those of Regeimbal et al (18) that DsbB-bound UQ assumes an anomalous state with a strong absorption peak at ϳ500 nm seem to provide important clues to the last question. Whereas Regeimbal et al showed that UQ in purified DsbB preparations exhibits a quinhydrone-like color, we provided compelling evidence that only special states of DsbB are able to elicit a UQ spectroscopic transition.…”
Section: Discussionsupporting
confidence: 53%
“…Bardwell and co-workers (18) suggested that UQ on DsbB constitutively forms a quinhydrone-type charge transfer complex consisting of a hydroquinone and a benzoquinone moiety and having a strong absorption at 505-510 nm. In contrast, we have shown that UQ undergoes a spectroscopic transition to exhibit an absorption peak at ϳ500 nm only when it is on DsbB in certain forms (11).…”
mentioning
confidence: 99%
“…Finally, we point out that at the final re-revision stage of this article, we came across an internet pre-release of a publication from Bardwell and coworkers (30). These authors described that wild-type DsbB is purple-colored and attempted to explain this observation in terms of the purple-colored quinhydrone, in which two stacked quinone molecules are involved.…”
Section: Uq Is Red-shifted Transiently During Reaction Betweenmentioning
confidence: 96%
“…Bacterium Escherichia coli has a series of disulfide bond formation factors (Dsb) 1 in the periplasmic space-plasma membrane region of the cell (1)(2)(3). DsbA is a periplasmic enzyme having a thioredoxin-like fold and is capable of donating its Cys 30 -Cys 33 disulfide to newly translocated substrate proteins (4 -7). Then, the two active site cysteines must be reoxidized for the continuing catalysis, and a plasma membrane protein, DsbB, is responsible for this reoxidation (8 -10).…”
mentioning
confidence: 99%
“…Regeimbal et al (17) reported that their DsbB preparation was purple-colored and discussed that it was due to the formation of quinhydrone-like charge transfer (CT) complex between UQ and hydroquinone that was also bound to DsbB. However, the lack of supporting evidence other than the similarity of the absorbance curve with that of quinhydrone made us question the likelihood of the involvement of the stacked two quinone rings for the spectroscopic behavior of DsbB.…”
mentioning
confidence: 99%